2016
DOI: 10.1111/mpp.12356
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide transcriptomic analyses provide insights into the lifestyle transition and effector repertoire of Leptosphaeria maculans during the colonization of Brassica napus seedlings

Abstract: Molecular interaction between the causal agent of blackleg disease, Leptosphaeria maculans (Lm), and its host, Brassica napus, is largely unknown. We applied a deep RNA-sequencing approach to gain insight into the pathogenicity mechanisms of Lm and the defence response of B. napus. RNA from the infected susceptible B. napus cultivar Topas DH16516, sampled at 2-day intervals (0-8 days), was sequenced and used for gene expression profiling. Patterns of gene expression regulation in B. napus showed multifaceted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 87 publications
6
91
0
Order By: Relevance
“…On the basis of visual observations, this condition was clearly met as Topas-wild plants exhibited clear symptoms of infection over the course of the experiment that culminated with the presence of extensive necrotic tissues at 11 dpi while the infection never extended beyond the point of inoculation in Topas -Rlm2 plants. Other studies have reported similar symptom progression at varying time points (Lowe et al, 2014; Haddadi et al, 2016), thus suggesting that experimental conditions can influence the rapidity with which L. maculans can infect its host. For this reason, it is critical to ensure that sampling procedures include enough replications that will capture an accurate biological variability within a condition.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…On the basis of visual observations, this condition was clearly met as Topas-wild plants exhibited clear symptoms of infection over the course of the experiment that culminated with the presence of extensive necrotic tissues at 11 dpi while the infection never extended beyond the point of inoculation in Topas -Rlm2 plants. Other studies have reported similar symptom progression at varying time points (Lowe et al, 2014; Haddadi et al, 2016), thus suggesting that experimental conditions can influence the rapidity with which L. maculans can infect its host. For this reason, it is critical to ensure that sampling procedures include enough replications that will capture an accurate biological variability within a condition.…”
Section: Discussionmentioning
confidence: 67%
“…dpi, days post inoculation; FPKM, Fragments per kilo-base of transcript per million mapped reads; 1, (Haddadi et al, 2016); 2, (Lowe et al, 2014) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its up-regulation in our in vitro experiment, Lema086540 was not retained as its log 2 -fold change was of only 1.8 and thus below our threshold. Two other genes (Lema006106, Lema084480), recently found to encode for SSP required for full or partial suppression of cell death (Haddadi et al, 2016) and located in GC-isochores were also up-regulated in presence of cycloheximide (Supplemental Table S2). In contrast, other avirulence genes located in AT-isochores such as AvrLm6 and AvrLm2 were not significantly affected by the cycloheximide treatment (data not shown).…”
Section: Antibiotics Of the Bleomycin Family Point To An Effect Of Phmentioning
confidence: 99%
“…Transcriptome sequencing has been used to analyse the interaction between B. napus and L. maculans (Lowe et al 2014;Haddadi et al 2016); both studies have used susceptible cultivars to determine pathogen and host gene expression. Such studies are useful to determine potential pathogenicity (e.g.…”
Section: Novel Genomic Approaches For Rapid Identification Of R Genesmentioning
confidence: 99%